Dusting, fragmenting, popcorning or dustmenting?. Issue 2 (March 2019) - Wenzel, Mike; Bultitude, Matthew; Salem, Johannes
Abstract : Purpose of review: The present review identifies the latest scientific investigations within the fields of fragmenting and dusting to discuss optimizing treatment. In addition, new settings such as 'popcorning ' are scrutinized carefully. Recent findings: During the past years, endoscopic techniques have continuously developed and changed the management of the treatment of kidney stones using ureteroscopy (URS). The most currently used energy source for stone disintegration is holmium laser lithotripsy. This technique offers different options for the surgeons to treat their patients suffering from kidney stones. Summary: URS with the holmium laser allows surgeons to use a variety of different strategies for treating urinary stones. There are two techniques which are most frequently used within this field: firstly fragmenting, using low frequencies and high pulse energy to break stones into small fragments before removal. On the other hand, dusting has been popularized in the field of endourology in recent years. This uses high frequencies and low pulse energy to form fine dust particles which then pass spontaneously down the ureter.